INFLUENCE OF RESISTIN ON THE COURSE OF ISCHEMIC HEART DISEASE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - A. T. Teplyakov; Sh. D. Akhmedov; T. Ye. Suslova; А. V. Andriyanova; A. V. Kuznetsova; N. V. Protopopova; V. V. Kalyuzhin; O. N. Nasanova (Бюллетень сибирской медицины, 2015)
Relevance. Through dermal coronary intravascular revascularization by means of stenting is an effective method of treatment CHD patients with the type 2 diabets. At the same time frequency of stents restenosing for this special cohort of patients is fluctuating from 12 by 40 %.Objective. To study prognostic significance of the new biomarker of intravascular inflammation of resisin in blood of CHD patients with DM 2 who suffered from stenting. Material and methods. In the study 60 patients (48 men and 12 women, in the middle age 60.9 years) with CHD and DM2 are included. The patients were divided into two groups: Patients with positive progress of comorbide pathology belonged to the first group (n = 30); in the second group (n =3 0) patients with unfavorable progress of cardiac vessel pathology were included. The further observation was carried during 12 months. Content of all the patients in blood of resistin with help of enzyme immunoassay analysis was determined, as well as lipid blood serum mixture and additional metabolic risk factors. By the indications control a coronary angiography was conducted. Restenosis of coronary arteries was counted as the narrowing of a coronal artery lumen of ≥70% in the place of an intervention.The result. Unfavorable flow, including restenosis of coronary arteries was revealed in 30 cases (50%). ROC-analysis showed great predictive significance of resistin – (area under a curve >5/35, Sensitivity 86.2, Specificit 70.0) in development of constrictive coronary atherosclerosis restenosis of coronary arteries after their stenosis.The conclusion. The study of resistin level in DM patients blood for the valuation of the disease prognosis and optimization of the tactics for choice of coronary pathology treatment seems expedient and informative.